Searching for an interstellar medium association for HESS J1534 − 571. Issue 1 (6th July 2018) - Maxted, Nigel I; Braiding, C; Wong, G F; Rowell, G P; Burton, M G; Filipović, M D; Voisin, F; Urošević, D; Vukotić, B; Pavlović, M Z; Sano, H; Fukui, Y
ABSTRACT: The Galactic supernova remnant $\rm{HESS\, J1534}-{\rm 571}$ (also known as G323.7 − 1.0) has a shell-like morphology in TeV gamma-ray emission and is a key object in the study of cosmic ray origin. Little is known about its distance and local environment. We examine Mopra 12 CO/ 13 CO(1–0) data, Australian Telescope Compact Array $\rm{H\, {\small I}}$, and Parkes $\rm{H\, {\small I}}$ data towards $\rm{HESS\, J1534}-{\rm 571}$ . We trace molecular clouds in at least five velocity ranges, including clumpy interstellar medium structures near a dip in $\rm{H\, {\small I}}$ emission at a kinematic velocity consistent with the Scutum–Crux arm at ∼3.5 kpc. This feature may be a cavity blown-out by the progenitor star, a scenario that suggests $\rm{HESS\, J1534}-{\rm 571}$ resulted from a core-collapse event. By employing parametrizations fitted to a sample of supernova remnants of known distance, we find that the radio continuum brightness of $\rm{HESS\, J1534}-{\rm 571}$ is consistent with the ∼3.5 kpc kinematic distance of the Scutum–Crux arm $\rm{H\, {\small I}}$ dip. Modelling of the supernova evolution suggests a ∼8–24 kyr age for $\rm{HESS\, J1534}-{\rm 571}$ at this distance.